2016
DOI: 10.5812/ircmj.24527
|View full text |Cite
|
Sign up to set email alerts
|

Designing Iranian Model to Assess the Level of Health System Responsiveness

Abstract: Background: Given the rapid pace of changes in community health needs and the mission of healthcare organizations to provide and promote the community's health, the growing need to increase health system responsiveness to people as a key element of observance and fulfillment of justice is felt more than ever. Objectives: This study was aimed at designing the native model of responsiveness for Iran and to validate the aspects of the proposed model. Materials and Methods: Our study had a cross-sectional design a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Communication, quality of basic amenities, and prompt attention received the highest scores and autonomy received a lower score in terms of their importance. These findings have been repeated in several previous studies in Iran (4,(12)(13)(14). It means that service recipients kept their preferences about the importance of responsiveness domains.…”
Section: U N C O R R E C T E D P R O O Fsupporting
confidence: 70%
See 1 more Smart Citation
“…Communication, quality of basic amenities, and prompt attention received the highest scores and autonomy received a lower score in terms of their importance. These findings have been repeated in several previous studies in Iran (4,(12)(13)(14). It means that service recipients kept their preferences about the importance of responsiveness domains.…”
Section: U N C O R R E C T E D P R O O Fsupporting
confidence: 70%
“…Studies in South Africa and Iran showed different clustering patterns of responsiveness (12,21). For example, "autonomy" in these studies was not conceptualized as a unique domain.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 70%
“…Subsequent studies have shown general agreement with the WHO elements, 35–38 though many proposed adaptations, for example additions of effective care, attention, access to care, 39 trust and coordination 34 and specified it for HIV or mental health. 40–42 Associations were also found between levels of reported responsiveness and type of health facility 37 43 or socioeconomic characteristics of patients, such as poverty, educational level and age, 23 40 42 44–46 echoing an argument that acceptability and trust barriers are disproportionately faced by socially disadvantaged groups.…”
Section: Resultsmentioning
confidence: 99%
“…Across items in this category, the WHO responsiveness tool has been validated and adaptations suggested – such as the addition of domains for education and information sharing [ 3 , 36 ], effective care [ 73 , 74 ], trust [ 73 , 75 ], coordination and responsibility [ 62 ]. Several authors have argued that the WHO’s conceptualization and tools have inherent inadequacies [ 69 , 76 , 77 ].…”
Section: Resultsmentioning
confidence: 99%